Building Work Culture in the Implementation of Electronic Medical Records to Improve the Effectiveness of Inpatient Services at Wedabay Medical Center, North Maluku - Edi Hartono; A. Rohendi; Yani Restiani Widjaja (CV. Civiliza Publishing, 2026)
The implementation of Electronic Medical Records (EMR) is a key component of healthcare digital transformation aimed at improving the effectiveness of inpatient services. The success of EMR implementation is strongly influenced by the work culture of healthcare professionals. This study aims to analyze the role of work culture in supporting EMR implementation, identify existing challenges, and propose improvement strategies at Weda Bay Medical Center, North Maluku. This study employed a qualitative case study approach. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using thematic analysis. The findings indicate that EMR implementation fosters a more disciplined, accountable, and digitally oriented work culture, leading to improved speed, accuracy, and coordination of inpatient services. However, challenges such as limited digital competence, resistance to change, and technical system issues remain. Continuous training, strengthened IT infrastructure, managerial support, and workflow adjustments are required to enhance effectiveness. The study concludes that an adaptive work culture is essential for effective EMR-based inpatient services.